Emotional Intelligence as a Predictor of Academic Performance in Hospitality Higher Education. Issue 2 (3rd April 2021) - Goh, Edmund; Kim, Hyun Jeong
ABSTRACT: This paper examines the relationship between emotional intelligence (EI) and academic performance among hospitality Master students. Using data on 60 hospitality Master students from an Australian University, EI scores, measured using the Trait Emotional Intelligence scale are regressed against self-reported grade point average (GPA) scores. The regression is significant, underlining that EI indeed plays an important role in academic performance. The four components of the Trait EI scale, namely Well-being, Self-control, Emotionality, and Sociability were distinguished, and each component was modeled as an independent driver of the GPA score. Of the four components, Emotionality was significant implying that hospitality Master students' ability to perceive and express emotions and use them to develop and maintain relationships is a critical predictor of GPA.